Pengaruh gaya kepemimpinan dan kompensasi terhadap kepuasan kerja pada perangkat Desa Bontolanra Kecamatan Galesong Utara Kabupaten Takalar - Nurjanna Nurjanna (ARKA INSTITUTE, 2022)
This study aims to examine and determine whether the variables of Leadership Style and Compensation have an effect on Job Satisfaction of Bontolanra Village Officials, North Galesong District, Takalar Regency. The population in this study was the entire village apparatus as many as 35 employees while the sample in this study was 100% of the total population, namely 35 employees. Questionnaire is a data collection technique used. The collected data were analyzed and then entered into multiple linear regression equations. The findings in this study indicate that partially and simultaneously the variables of leadership style and compensation have a positive and significant effect on job satisfaction of Bontolanra village officials, North Galesong District, Takalar Regency. That is, every leadership style and compensation is improved, it will increase employee performance and job satisfaction and vice versa. So that the hypothesis in this study is accepted.